(untitled) (Third Sector Social Economic Review, 2022)
Purpose: In this study, it is aimed to empirically reveal whether there is a mediating effect of workplace happiness in the effect of authentic leadership on work productivity. Design/methodology/approach: Data were collected from the employees of a company operating in the textile sector in a province in Turkey using the survey technique. Three scales were included in the questionnaire form used in the research. Results: According to the research results; authentic leadership positively affects happiness at work. Happiness at work has a positive effect on work productivity. The mediation level of happiness at work is at the level of partial mediation in the effect of authentic leadership on work productivity. The effect of authentic leadership on work productivity was found to be statistically insignificant. Research Limitations: The limitation of the research is that the research is carried out only on the employees of a private company operating in the textile sector in one province. Conducting the research on a single industry and firm may limit the ability of the authors to draw definite conclusions. Originality/value: The research is important in terms of analyzing whether there is a relationship between employees’ perceptions of authentic leadership and work productivity, between perceptions of authentic leadership and happiness at work, as well as between perceptions of happiness at work and work productivity. The analysis of these variables together for the first time, together with the mediation effect, reveals the original value of the study.